Nitrogen emissions in latin america: a conceptual framework of drivers, impacts, and policy responses - Cunha-Zeri, G., Ometto, J. (My University, 2021)
Reactive nitrogen has both positive and negative effects on environment and human health. The use of nitrogen fertilization enabled raising crops and livestock to feed an increasing world population, but at the same time resulted in a succession of unwanted impacts occurring through air, soil, and water, with detrimental consequences for all mankind. Nitrogen pollution is one of Latin America's most widespread and challenging environmental problems and is caused due to excess of nitrogen emissions from productive activities, especially agriculture, to attend a growing demand for food and energy. Here, we develop a conceptual framework of nitrogen emissions in Latin America to better understand the complexity of nitrogen dynamics in the region, the diverse drivers, and potential harms to environment and human health, as well as to support the formulation of adequate mechanisms to deal with the adverse impacts while increasing the benefits. Thus, our objective was to generate a functional tool not just for nitrogen scientists, but also for decision and policy makers. Using Brazil as an example, our main finding was that the increase in N emissions is due to demand drivers (demand for food, energy, and housing, connected with socioeconomic factors), while preparing and implementing a successful response to solve the N pollution problem depends entirely on the structural drivers (political and institutional factors, as governance issues). We highlighted the crucial role of political decision and institutional forcefulness in designing and implementing suitable policy instruments to handle the duality of nitrogen use. This finding prompts us to rethink about the (often non-existent) policy responses and the challenge for Latin American countries to deal with the nitrogen dilemma, &ldquotoo much or too little of a very important nutrient&rdquo. Highlights A conceptual framework of nitrogen emissions drivers in Latin America is proposed. Nitrogen pollution in Latin America is a byproduct of productive activities. Nitrogen drivers are related to both socioeconomic and political factors. Policy instruments for sustainable nitrogen use are very limited.
Keywords: Nitrogen pollution; Reactive nitrogen; Nitrogen management; Conceptual framework; Agricultural systems; Demand drivers; Structural drivers; Policy responses